Collagen Extraction from Red Snapper (Lutjanus malabaricus) Scales via Hydroextraction: Toward Nanocollagen Development - Mayangsari, Cholivia; Mahasri, Gunanti; Shofy Mubarak, Ahmad (Journal of Marine and Coastal Science, 2025)
Generally, collagen is isolated using acid, base and enzymatic hydrolysis methods. However, this has the constraint of the length of time for the release of procollagen to produce collagen. Acetic acid hydrolysis combined with the hydroextraction method is one alternative to produce quality collagen. The use of acetic acid in the extraction of red snapper scales (Lutjanus malabaricus) will produce H+ ions to release procollagen in the raw material. The study aims to evaluate the potential of red snapper (L. malabaricus) scales as a collagen source through the hydroextraction method for the development of nanocollagen formulations. This study used a completely randomized design (CRD). Isolation of red snapper scales collagen using acetic acid solvent concentrations of 1 M; 1.5 M and 2 M with a hydrolysis time of 2 hours and hydroextraction for 2 hours with three repetitions. The parameters observed in this study were the proximate of collagen raw materials, collagen yield, and collagen amino acids. The data analysis results were tested statistically using Analysis of Variance (ANOVA) followed by Tukey's further test. The best result of collagen isolation from red snapper (L. malabaricus) scales was achieved using 2 M acetic acid hydrolysis combined with hydroextraction. This study demonstrated that the combination of different acetic acid concentrations with hydroextraction had a significant effect (P<0.05) on collagen yield parameters. The amino acid content consisted of 22.37% glycine and 12.45% proline. These findings indicate that red snapper (L. malabaricus) scales have the potential to be developed as a raw material for nanocollagen developments.